Auto-Recognition of Chamfer Features by Rule Based Method and Auto-Generation of Delta Volume - Kataraki, P.S.; Abu Mansor, M.S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Integration of computer aided process planning (CAPP) in CAD/CAM contributes to a successful product manufacturing and to achieve an automated process planning, auto-recognition of chamfer features of a product is necessary. An effort has been made (i) to automatically recognize the chamfer features of regular form and freeform computer aided design (CAD) models using rule based method and (ii) to auto-generate delta volume (DV) from stock model. Based on the conditions described the chamfer features of an input CAD model are successfully recognized and delta volume required to be machined in chamfering process is obtained from stock model.